Qualification, knowledge and experience of dispensers working at community pharmacies in Pakistan (Pharmacy Practice, 2011)
Pharmacies are managed by a variety of dispensers in terms of qualification, knowledge and experience in Pakistan.Objective: The study aimed to document the state of knowledge, experience and qualification of dispensers working at community pharmacies in Pakistan.Methods: A comparative cross sectional study was conducted at a randomly selected sample of 371 pharmacies in the three cities of Pakistan. A structured questionnaire for data collection was developed and finalized by focused group discussions and pilot testing. The data was coded, entered and analyzed by using SPSS Version 16. Kruskal-Wallis and Mann-Whitney tests (p≤0.05) were performed to find out differences.Results: Out of total sample of 371 pharmacies, 31.8 % (118) were in Islamabad, 32.4 % (120) in Peshawar and 35.8 % (133) were in Lahore. Fifty percent of the respondents had correct knowledge of range of room temperature at which medicines should be stored. Only 11.1% (41) of the respondents knew about OTC (over the counter drugs) which can be sold without prescription while 5.9 % (22) of the respondents were aware of POM (prescription only medicines) which can be only sold on a valid prescription. While 87.6% (325), 88.1% (327), 58.7% (318) and 95.7 % (355) of the respondents did not know the meaning of the dispensing abbreviations such as ‘h.s’, ‘q.d’, ‘sos’ and ‘p.r.n’. The respondents did not know correctly the status of Deltacortil® (Prednisolone), Septran® (Sulfamethoxazole) and Fansidar® (Pyrimethamine and Sulfadoxine) either as OTC or POM in 26.7% (99), 64.2% (238), and 44.5 % (165) of the cases, respectively. There was a significant difference (p≤0.05) in knowledge of dispensers regarding storage temperature, prescription terminologies and status of medicines having different level of qualification and experience.Conclusions: The overall knowledge and training of dispensers working at community pharmacies is inadequate in Pakistan. However, pharmacists had relatively better knowledge regarding storage temperature, prescription terminologies and status of medicines as compared to pharmacy assistants, diploma holders and salesperson. Keywords: Pharmacists' Aides. Professional Competence. Pharmacies. Pakistan.